A História da Filosofia é ou não Filosófica? - Aubenque, Pierre (Princípios: Revista de Filosofia (UFRN), 2010)
Ensaiooriginalrnfntepublicadosob0 titulo de I;estdredelaH1ilosqJhieest-eUeoo ~?ilietNcn.in(crg. Bart:maCassin):NooGra:setLeuTsMaiemes(Cd. C11eminsdef seej, RJ.17-36,EdnmsduSew1.PaIis 1992.Apiliica;;aodestatraduc;flo foifeitacornagentilpe!111issaodeEditia-rsduSeuiL